Berberine Protects Mice Against Dextran Sulfate Sodium-Induced Colitis by Activating mTORC1 Pathway - Li, Qingjun; Qu, Xinyan; Pang, Xiaogang; Song, Yue; Chen, Liyuan; Xiao, Qiuyue; Sun, Linlin; Wang, Xiaolong; Zhang, Huimin; Qi, Dongmei; Wang, Zhenguo (Frontiers in Pharmacology, 2019)
Berberine is a plant alkaloid which can be extracted from many Chinese herbs. It has been reported that berberine could protect mice from ulcerative colitis but the mechanism remains unclear. The current study was to determine the potential mechanism by which berberine exhibit its anti-inflammatory function. Mice with colitis induced by dextran sulfate sodium (DSS) was administrated with berberine at 50mg/kg by gavage. Berberine significantly increased the proportion of regulatory T cells (Treg cells). The targeted metabolomics analysis was then performed to find that glutamine and glutamate metabolism played an important role in the process of regulating immune response. mTOCR1 pathway was reported to closely relate with glutamine metabolism. As a result, the relative expression levels of downstream effector genes of mTOCR, was further determined and data obtained showed that berberine could significantly increase the relative expression levels of S6K1 and 4EBP1. In addition, rapamycin was used to inhibit mTORC1 signaling and it was found that colon length, disease associated index (DAI) and proportion of Treg cells of mice in Rapamycin-DSS group were not different from that of mice in Rapamycin/Berberine-DSS group. Together, these results suggest that berberine exhibit significant protective effects against DSS-colitis by activating the mTORC1 pathway to increase the proportion of Treg cells.